Normal weight and waist obesity indicated by increased total body fat associated with all-cause mortality in stage 3–5 chronic kidney disease - Shen, Feng-Ching; Chen, Mei-En; Wu, Wei-Tsung; Kuo, I-Ching; Niu, Sheng-Wen; Lee, Jia-Jung; Hung, Chi-Chih; Chang, Jer-Ming; Hwang, Shang-Jyh (Frontiers in Nutrition, 2022)
Patients with chronic kidney disease (CKD) demonstrate a survival benefit with a high body mass index (BMI); this is the obesity paradox. Central obesity has a higher prognostic value than BMI, even in those with normal weight. Whether total body fat percentage (TBF%) provides more information than BMI and waist circumference (WC) remains unknown. We included 3,262 Asian patients with stage 3–5 CKD and divided these patients by TBF% and waist-to-height ratio (WHtR) quartiles (Q1–Q4). TBF% was associated with BMI, WC, nutritional markers, and C-reactive protein. In all patients, BMI but not TBF% or WHtR demonstrated a survival paradox. In patients with BMI <25 kg/m2, but not in those with BMI ≥ 25 kg/m2, TBF% Q4 and WHtR Q4 were associated with all-cause mortality, with hazard ratios [HRs; 95% confidence intervals (CIs)] of 2.35 (1.31–4.22) and 1.38 (1.06–1.80), respectively. The HRs of TBF% Q4 for all-cause mortality were 2.90 (1.50–5.58) in patients with a normal WC and 3.81 (1.93–7.50) in patients with normal weight and normal WC (All P for interaction < 0.05). In conclusion, TBF% can predict all-cause mortality in patients with advanced CKD and a normal weight, normal WC, or both.